2018
DOI: 10.3758/s13415-018-0634-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural time course and brain sources of facial attractiveness vs. trustworthiness judgment

Abstract: Prior research has shown that the more (or less) attractive a face is judged, the more (or less) trustworthy the person is deemed and that some common neural networks are recruited during facial attractiveness and trustworthiness evaluation. To interpret the relationship between attractiveness and trustworthiness (e.g., whether perception of personal trustworthiness may depend on perception of facial attractiveness), we investigated their relative neural processing time course. An event-related potential (ERP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
(79 reference statements)
3
12
0
Order By: Relevance
“…Beyond the early representation of facial attractiveness, we show that EEG responses also carried a sustained neural attractiveness signal. These sustained effects are in line with the later modulations of facial attractiveness stressed by some EEG studies [27][28][29][30][31][32][33][34][35][36][37] . These studies may not have found earlier differences related to facial attractiveness for varied reasons: Apart from the lower sensitivity offered by univariate ERP analyses, individual studies used largely orthogonal tasks, had small sample sizes, or did not specifically look for N170 differences.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Beyond the early representation of facial attractiveness, we show that EEG responses also carried a sustained neural attractiveness signal. These sustained effects are in line with the later modulations of facial attractiveness stressed by some EEG studies [27][28][29][30][31][32][33][34][35][36][37] . These studies may not have found earlier differences related to facial attractiveness for varied reasons: Apart from the lower sensitivity offered by univariate ERP analyses, individual studies used largely orthogonal tasks, had small sample sizes, or did not specifically look for N170 differences.…”
Section: Discussionsupporting
confidence: 82%
“…Twenty-four adults (mean age 19.8, SD 1.6; 20 female) participated in the study. This sample size was comparable with the sample sizes of previous EEG studies on facial attractiveness [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , which tested a median of 20 participants, and an average of 24.6 participants. All participants had normal or corrected-tonormal vision.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…In this way, a ROI was defined as a set of at least 15 nearby solution points for which ANOVA results yielded Cue × Valence interaction effects with associated p values below .01. This strategy to define a ROI was preferred over other methods because it reduces to some extent the risk for false positive while still retaining power to detect relevant effects (for similar strategies: Beltrán et al., 2018; Bernasconi et al., 2011; Buetler et al., 2014; Calvo et al., 2018). For each ROI fulfilling this definition, a single value was obtained by computing a weighted average of the current source magnitudes of all its solution points, using as weights the result of dividing the F ‐value in each solution point by the F ‐value for the solution point showing the strongest interaction effect.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, FA also affects various cognitive processes, including attention (for a review, see Lindell and Lindell, 2014), memory (e.g., Wiese et al, 2014), and even has implications in brain activity (Hahn and Perrett, 2014;Siuda et al, 2015). It also seems to have a neural processing time course different from the perception of other attributes (Calvo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%